2007
DOI: 10.1002/prca.200700264
|View full text |Cite
|
Sign up to set email alerts
|

The proteomic approach in Parkinson's disease

Abstract: Parkinson's disease (PD) is a complex, multifactorial neurodegenerative disease affecting about 2% of the population over 65 years. Etiopathogenetic mechanisms of PD are not fully understood, although a number of factors contributing to the selective degeneration of substantia nigra neurons have been identified, including mitochondrial dysfunction, proteasomal impairment, oxidative stress, excitotoxicity, and inflammation. Although a global view of the disease at the molecular level can be obtained only from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Although the proteomic approach in neuroscience research is very recent, several papers have been published in the last 4 years on the investigation of pathogenetic mechanisms of neurodegenerative disorders by proteomics [68][69][70]. Nevertheless, a small number of reports dealt with the proteomic investigation of human SNpc tissue [20,[71][72][73][74][75].…”
Section: Protein Expression Analysis In Sporadic Pd Patientsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the proteomic approach in neuroscience research is very recent, several papers have been published in the last 4 years on the investigation of pathogenetic mechanisms of neurodegenerative disorders by proteomics [68][69][70]. Nevertheless, a small number of reports dealt with the proteomic investigation of human SNpc tissue [20,[71][72][73][74][75].…”
Section: Protein Expression Analysis In Sporadic Pd Patientsmentioning
confidence: 97%
“…Currently, a few studies have been reported examining animal models of PD using proteomics [68][69][70]. To date, most information regarding the mechanisms involved in the pathogenesis of PD has gained from the study of transgenic animal models.…”
Section: Protein Expression In Transgenic Animal Models Of Pdmentioning
confidence: 99%
“…In the present study, we investigate the dopamine effect on the expression pattern of cellular proteins in the human catecholaminergic neuroblastoma cell line SH‐SY5Y, overexpressing α‐synuclein. A proteomic analysis is expected to identify cellular alterations that are associated with dopamine treatment and modulated by α‐synuclein overexpression, without any a priori hypothesis [4,11,12]. SH‐SY5Y cells couple good dopamine transporter activity with a low activity of the vesicular monoamine transporter type 2, such that cytoplasmic dopamine concentration may be raised by the administration of exogenous dopamine in the culture medium [7,13–15].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a complex, multifactorial neurodegenerative disease affecting about 3% of the population over 65 years. It is often characterized by a gradual degeneration of dopaminergic neurons in the midbrain substantia nigra pars compacta (SNc). , The proteins identified in brain may be related with PD, based on the reference reported …”
Section: Resultsmentioning
confidence: 99%